Psychological well-being and coping strategies in dealing with COVID-19 in university students - Narváez, Jonnathan Harvey; Obando-Guerrero, Lina María; Hernández-Ordoñez, Karen Melisa; De la Cruz-Gordon, Eliana Katherine (Universidad y Salud, 2021)
Introduction: The pandemic caused by COVID-19 is an unprecedented worldwide situation. It is predicted that COVID-19 will have a significant impact on humans as it can cause changes in their dynamics, habits, and routines that affect their psychological well-being and coping strategies. Objective: To identify whether there is an association between psychological well-being and the different coping strategies in confronting the psychological impact of COVID-19 in university students. Materials and methods: A quantitative, non-experimental, descriptive-correlational, and cross-sectional study was carried out on a sample of 201 university students from the southwestern region of Colombia. The Ryff ‘s Psychological Well-Being Scale and the Modified Coping Strategies Scale (EEC-M) were used. Data analysis was performed with SPSS software. Results: A statistically significant direct association was found between psychological well-being and coping strategies, problem solving, seeking social support, religion, cognitive avoidance, positive reassessment, and denial. Conclusion: Coping strategies are related to the psychological well-being of students, so their use can provide important inputs to face the psychological consequences generated by the pandemic.